Writing time : studies in serial literature, 1780-1850 - Franzel, Sean (Ithaca [New York] : Cornell University Press and Cornell University Library, 2023)
"This book is a study of time and seriality in the nineteenth-century periodical."--
Bertuch's cultural journalism -- Goethe's "The Roman carnival" and its afterlives -- Caricature and ephemeral print in "London und Paris" -- Jean Paul's paper festivals -- Jean Paul's incomplete works -- Waiting for the revolution: Ludwig Börne -- Heine's serial histories of the revolution -- Serial literature's untimely afterlives?
"A Signale Book."
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on November 10, 2023).
JSTOR
Keywords: Time in literature; Time -- Philosophy -- History -- 19th century; Serial publications -- Europe -- History -- 19th century; Authors and readers -- History -- 19th century; Écrivains et lecteurs -- Histoire -- 19e siècle.; Temps -- Philosophie -- Histoire -- 19e siècle.; Temps dans la littérature.; Publications en série -- Europe -- Histoire -- 19e siècle.; LITERARY CRITICISM / Books & Reading; Authors and readers; Serial publications; Time in literature; Time -- Philosophy; Europe; Germany; Literature: history & criticism; Museology & heritage studies; Historiography; Media Studies; 1800-1899; Zeitgeschichte, nineteenth century cultural journalism, periodical studies, Koselleck, techniques of temporalization, history of the present, German-language authors; Electronic books; History